2002
DOI: 10.1007/s001980200089
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Supplement and Bone Medication Use in a US Medicare Health Maintenance Organization

Abstract: This study was conducted to determine the prevalence of the use of calcium supplements and of prescription medications to prevent or treat osteoporosis in men and women in a large New England Medicare Health Maintenance Organization (HMO). A two-page diet, medication use and medical history questionnaire was sent to a random sample of 9000 out of 82 985 members and 2932 (32.6%) responded. Over 97% of the participants were Caucasian and 64.7% were female. The mean ages of the men and women were 74.4+/-5.8 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
4
7
0
Order By: Relevance
“…This confounding by indication may mask an inverse association between milk intake and hip fracture risk in women in particular because they are more likely to receive advice to increase their calcium intake. (28) However, this issue most likely relates to the use of calcium supplements and less to an increased milk intake. Consistent with this idea, in the Nurses' Health Study, the exclusion of women with a history of diagnosed osteoporosis did not appreciably affect the association between milk intake and fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…This confounding by indication may mask an inverse association between milk intake and hip fracture risk in women in particular because they are more likely to receive advice to increase their calcium intake. (28) However, this issue most likely relates to the use of calcium supplements and less to an increased milk intake. Consistent with this idea, in the Nurses' Health Study, the exclusion of women with a history of diagnosed osteoporosis did not appreciably affect the association between milk intake and fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…While this phenomenon may be due to other sex-related factors involved in the pathogenesis of osteoporosis, future studies should assess whether a higher prevalence of calcium supplement use among women compared with men played a role. 37 In summary, we observed that PPI therapy is associated with a significantly increased risk of hip fractures, with the highest risk seen among those receiving high-dose PPI therapy. Osteoporotic fractures are common among the elderly population, and they entail considerable morbidity and mortality.…”
Section: Commentmentioning
confidence: 80%
“…For example, in a Medicare health maintenance organization (HMO) in the Boston area in 2002, bone medication use was <20% in women in all age groups [25]. In the Pennsylvania Medicaid population, age 50 and older, Lee et al [26] found that the overall prevalence of anti-osteoporosis medication use was under 15% in December 2002.…”
Section: Discussionmentioning
confidence: 99%
“…However, prescribing patterns clearly indicate that older men are undertreated for osteoporosis. In a largely Caucasian (>98%) Medicare HMO population surveyed in 2002, only 2% of the men reported taking a prescription medication for osteoporosis [25]. Among men with a hip fracture (all of whom would qualify for treatment), use of prescription drugs has increased since 1995, but it remains low, with less than one third receiving therapy in the 6-to 12-month period after the fracture [30,31].…”
Section: Discussionmentioning
confidence: 99%